THE LEXICAL DIFFERENCES IN MADURESE VARIETIES SPOKEN BY PEOPLE IN SITUBONDO REGENCY - Rhofiatul Badriyah, 121211231127 (2016)
One of the characteristics of Madurese variety used in Situbondo Regency is the lexical differences. Focusing on the Madurese variety used by people to communicate in daily life, this study aimed to describe the lexical differences and to reveal the status of the lexical differences. Five villages were chosen as the observation points of the study: Demung (OP1), Tanjung Pecinan (OP2), Sumberwaru (OP3), Curah Tatal (OP4), and Taman (OP5). Using a word list of 450 words, a total of fifteen informants were interviewed. Beside interview, some activities included recording, note taking, and crosschecking were also carried out to obtain the data. The data were then analyzed and calculated using dialectometry formula. The results show that out of 450, there are 133 lexical differences. The percentage of the lexical differences between OP 1 snd OP2 reaches 52. 6% which means that the varieties used in the two OPs are different dialects. Meanwhile, index percentage in six other compared OPs indicates that they have different sub-dialect status. The percentage of the lexical differences between OP 2 and OP3 is 42. 1%, OP3 and OP4 is 42. 1%, OP4 and OP5 is 45. 9%, OP1 and OP5 is 34. 6%, OP2 and OP5 is 40. 6%, and OP2 and OP5 is 42. 9%. In conclusion, the status of the lexical differences of the Madurese varieties spoken by people in Situbondo Regency includes different dialects and different subdialects.